Avaliação da influência de diferentes solos na degradação de hidrogel de amido modificado com EDTAD - Moura-Murari, Adriana Sheyla (Universidade Federal de São Carlos, 2024)
This study evaluated the influence of the degradation of a new hydrogel produced from EDTAD-modified starch in two different soils and the bacterial community involved in this process. The soils are an argisol, which was called "soil A", and a red oxisol, called "soil B". The soils were characterized and the argisol presented 12.4% of organic matter and pH 5.1, and the red oxisol, 11.6% of organic matter and pH 4.6. The argisol also has more residual soil moisture and higher amounts of micro and macronutrients, such as phosphorus, calcium, magnesium, and other physical characteristics such as cation exchange capacity, while the oxisol has more calcium phosphate and aluminum. The biodegradation test was performed using the Bartha respirometric method, measuring biodegradation by titrating the KOH solution that captured theCO2 emitted by the microbiota present in the respirometers with soil and hydrogel sample. It was observed that the biodegradation of the hydrogel in the argisol was more efficient, but more thorough and linear. After the end of the degradation experiments, the soil DNA was extracted from the DNA and sequenced for a qualitative analysis of the existing microorganisms. 340 to 480 genetic profiles were found in each one of the samples, with the highest diversity being in the soil sample B with hydrogel post-biodegradation, and the lowest, in soil A post-biodegradation. The fact that two different soils were used in this study shows how important their physicochemical properties are in the activity of the microorganisms present in the biodegradation process, since the sample incubated in the soil, richer in organic matter (albeit with a slight difference), micro and macronutrients and higher acidity obtained a more complete and uniform biodegradation, while soil B, with opposite characteristics, obtained a lower biodegradation of the hydrogel, even though it was incubated for a longer time, a fact that may have been influenced by a higher concentration of aluminium, which influences a lower bacterial activity.
Evaluation of the influence of different soils in the biodegradation of an EDTAD-Modified starch hydrogel
Evaluation of the Influence of different soils in the biodegradation of an EDTAD-Modified starch hydrogel
Keywords: Hidrogel; Hydrogel; Biodegradation Microorganisms; Soils; Biodegradação; Microrganismos; Solos; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; CIENCIAS BIOLOGICAS; OUTROS; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::MICROBIOLOGIA APLICADA E ENGENHARIA SANITARIA